CAUSES OF FLOODS AND FLOODS AND THEIR RAILWAY AND ECONOMY INFLUENCE ON CONSTRUCTION - R, Razikov; Abdazimov, Shavkat; D, Saidov; Muxtor, Amirov (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: This article discusses the issue of methods of ensuring safety in emergency situations of a natural nature in railway transport, settlements and infrastructure of the mountainous regions of the Republic, about landslides occurring in the mountainous and mountainous regions of the Republic, leading to road destruction. Especially when transporting dangerous goods by different modes of transport. The article considers the issue of natural emergencies that occurs in the spring and autumn seasons, resulting in mudflows, landslides and landslides, where the railways pass, settlements and other infrastructures are located.